Jumlah dan Ukuran Nodul Tumor Kolorektal Berbanding Lurus dengan Ekspresi Siklooksigenase-2 (THE CORRELATION OF THE NUMBER AND THE SIZE OF COLORECTAL TUMOR NODULE WITH CYCLOOXYGENASE-2 EXPRESSION) - Yulianty, Risfah; Nufika, Riska; Widyarini, Sitarina (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
Study chemically induced colon cancer with 1,2-Dimethylhydrazine (DMH) has been widely used.DMH induction to rodentia as animal model have been similarity with colon cancer morphlogy of human.Cyclooxygenase-2 (COX-2) are important enzymes that affect carcinogenesis.COX-2can be induced byvarious stimuli, including inûammation, growth factors, and cytokines produced by tumor cells. The aim ofthis study is  to investigate the correlation between the expression  of COX-2 and the doses variation ofDMH, the number and the size of colorectal tumor nodule.Six male Wistar rats were randomly divided into 4 groups each group consists of six rats.  Group I is control group.  Group II, III, and IV were given 20, 40,and 60 mg/kg BW of DMH respectively.  DMH  was subcutaneously injected in the hip area, once a week for15 weeks.  All animals were sacrificed at week 26th, the colon were removed and fixed in 10% bufferformalin for macroscopic and microscopic examination.  The results of this study showed that there is acorrelation between various doses of DMH  (P<0.05) with number of tumor nodule but not with the size ofcolorectal tumor nodule (P>0.05). Microscopic examination by using HE staining shows that inductionwith doses variation ofDMHresultin different morphololical form of tumour tissue.  Induction of 20, 40,and 60 mg/kg BW DMH result in adenoma(100.00%),adenoma and adenocarcinoma (33.30% and 66.67%),and 100.00% adenocarcinoma respectively.  The happens of COX-2 also correlate with in this studythatexpression of COX-2 correlate with the number and size of colorectal tumor nodule (P<0.05). However,there is no correlation between COX-2 expressionand doses variation of DMH.  In conclusion, there is adose-dependent response in the number and the size of colorectal tumor nodule.
Keywords: colorectal carcinoma, DMH, COX-2 expression